Penerapan Message Diggest Algorithm MD5 untuk Pengamanan Data Karyawan PT. Swifect Berbasis Desktop - Muhammad Rafiq Zayana; Iskandar Fitri; Fauziah Fauziah; Aris Gunaryarti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
In the era of Society 5.0, technological progress is unstoppable. Technological advances in the era of society 5.0 have become the main needs of humans in helping daily work. Technology is used as a medium for finding information to transportation tools that are integrated with the intervention of digital technology. Almost every company has technology to support their business development needs. And especially in agencies in this era, employee data is also processed using technology, but with the integration of employee data into technology, a lot of sensitive data must be protected in order to avoid misuse by irresponsible people. Therefore, the main objective of this research is to develop the application of the Message Diggest Algorithm (MD5) Cryptography Algorithm in employee data applications. This application is very appropriate to make it easier for companies to manage their employee data and ensure data security. To secure sensitive data from each employee, the process carried out is by encrypting each sensitive data so that it is not easy to read by others who have no interest or authority over the data. And the desktop-based application was made using Visual Basic. The research was carried out with two methods, namely the method to test the compilation speed of MD5 and to test the validation of the decrypted data from the MD5. And from the results of the study, the average speed of 500-515 milliseconds and data consistency obtained valid results from all tests.